Gestational weight gain and adverse pregnancy outcomes: a prospective cohort study. Issue 9 (2nd September 2020) - Wu, Yuelin; Wan, Sheng; Gu, Shengyi; Mou, Zhengqian; Dong, Lingling; Luo, Zhongcheng; Zhang, Jun; Hua, Xiaolin
Abstract : Objective: To assess the associations of gestational weight gain (GWG) in early and late pregnancy with subsequent risks of adverse pregnancy outcomes in Chinese women. Design: Prospective cohort study. Setting: Shanghai, China. Participants: We studied 2630 nulliparous singleton pregnant women with complete data on weight gain in early (≤17 weeks of gestation) and late (>17 weeks) pregnancy in the Shanghai Birth Cohort. Methods: GWG was standardised into z-scores by gestational age and categorised as low (z-score <−1), normal (−1 to +1) and high (>1). The adjusted relative risks (aRRs) and 95%CIs were estimated through log-binomial regression models. Interaction effects between GWG and some other adjustment factors were tested, further stratified analyses were performed separately where interaction terms were significant. Outcome measures: Adverse maternal and neonatal outcomes. Results: Independent from GWG in late pregnancy, higher GWG in early pregnancy was associated with higher risks of gestational diabetes mellitus (aRR: 1.66; 95% CI: 1.11 to 2.48), caesarean section (aRR: 1.21; 95% CI: 1.05 to 1.39) and prolonged hospitalisation (aRR: 1.56; 95% CI: 1.03 to 2.38). Higher GWG in late pregnancy was independently associated with higher risks of caesarean section (aRR: 1.24; 95% CI: 1.09 to 1.41), large for gestational age (aRR: 2.01; 95% CI: 1.50 to 2.7) and macrosomia (aRR: 1.90; 95% CI: 1.30 to 2.78). In addition, the risk of gestational hypertension increased significantly with increased total GWG (aRR: 1.78; 95% CI: 1.14 to 2.76). The effects of GWG in late pregnancy on maternal and neonatal outcomes were significantly different between the women bearing a female and the women bearing male fetus. Conclusion: The GWG associations with adverse pregnancy outcomes differ at early and late pregnancy, and there may be effect modification by fetal sex in the association of GWG in late pregnancy with some pregnancy outcomes.